Analysis of The Effect of Monetary Policy on Government Sharia Securities (SBSN) in Indonesia - Juaris Juaris; Raja Masbar; Chenny Seftarita (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2018)
Outstanding Government Sharia Securities (SBSN) in Indonesia from the first published on 2008 continued to experience significant growth. Monetary indicators often associated with capital markets are inflation, exchange rate and interest rate (BI Rate) show a fluctuating pattern, these factors can inhibitSBSN growth.This study aims to analyze the effect of monetary policy(inflation, exchange rate and BI Rate) on Government Sharia Securities (SBSN) and the contribution of Government Sharia Securities (SBSN) tothe state budget(APBN). Using monthly time series data from January 2010 until July 2016 and Autoregressive Distributed Lag (ARDL), the estimation results conclude that there is a co-integration in the models studied. While the estimation result of ARDL shows in the long term, exchange rate significantly has an effect on SBSN. While inflation and BI Rate have no significant effect on SBSN either in the short or long term. This study also shows the positive contribution of SBSN as deficit financing and development project. Therefore, the government must optimize the state sukuk by increasing the issuance of state sukuk in the structure of the state budget and supported by the control of inflation and exchange rate. For investors can take advantage of the state sukuk to invest, this is consistent with the insignificant effect of interest rate so that the investment is safe with sharia principles.